1997
DOI: 10.1128/jvi.71.10.7312-7317.1997
|View full text |Cite
|
Sign up to set email alerts
|

Carboxy-terminal cleavage of the human foamy virus Gag precursor molecule is an essential step in the viral life cycle

Abstract: Foamy viruses (FVs) express the Gag protein as a precursor with a molecular mass of 74 kDa (pr74) from which a 70-kDa protein (p70) is cleaved by the viral protease. To gain a better understanding of FV Gag protein processing and function, we have generated and analyzed mutants in the C-terminal gag region of an infectious molecular clone. Our results show that p70 is an N-terminal cleavage product of pr74. However, we were unable to identify a p4 molecule. A virus mutant expressing p70 only was found to be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…Unlike Gag proteins from orthoretroviruses which are cleaved and processed into capsid, matrix and nucleoprotein, FV Gag proteins are only partially cleaved at the C-terminus generating two species: a long and a shorter proteins that only differ by 4 kDa, both being incorporated in the virion (Enssle et al, 1997). They contain three Glycine and arginine-rich regions (the GR boxes) important for the correct FV assembly and the nuclear localization of Gag (Lee and Linial, 2008;Yu et al, 1996b), the role of which is still not elucidated.…”
Section: Fv Life Cyclementioning
confidence: 99%
“…Unlike Gag proteins from orthoretroviruses which are cleaved and processed into capsid, matrix and nucleoprotein, FV Gag proteins are only partially cleaved at the C-terminus generating two species: a long and a shorter proteins that only differ by 4 kDa, both being incorporated in the virion (Enssle et al, 1997). They contain three Glycine and arginine-rich regions (the GR boxes) important for the correct FV assembly and the nuclear localization of Gag (Lee and Linial, 2008;Yu et al, 1996b), the role of which is still not elucidated.…”
Section: Fv Life Cyclementioning
confidence: 99%
“…The three GR boxes involved in distinct phases of viral replication (49,64,78) were present in all isolates. The viral protease-dependent cleavage site RAVN/TVTQ, which allows the generation of the p68 Gag subunit from the full Gag (57), which is essential for subsequent correct particle formation (19,80), displayed high homology among all isolates. Interestingly, basic residues in the Gag protein are rare and mainly represented by arginines instead of lysines, in deep contrast to orthoretroviruses, as recently reported (44).…”
Section: Isolation and Subsequent Complete Sequencing Of Sfv Strains mentioning
confidence: 99%
“…However, at least some of the Gag molecules have to be cleaved to obtain infectious virus particles. 6,40 In summary, we demonstrate an essential role for region aa 107-143 for polymerase but not protease activity, whereas the connection subdomain is important for substrate affinity, protein stability and proper function of the RT. Furthermore, our data on PR activation show that the full length PR-RT including the RNase H domain is required for PR activity.…”
Section: Discussionmentioning
confidence: 72%
“…However, analysis of the protein composition of virus particles demonstrated that in FVs Gag cleavage is only partial, whereas Pol is processed completely into PR-RT and IN. [6][7][8][9] Therefore, we wanted to determine, whether in vitro one of the two cleavage sites is preferred and cleaved Properties of Foamy Virus PR-RT with higher efficiency by wt PR-RT. Two substrates were used, containing either the natural Gag or Pol cleavage site between the proteins GB1 and GFP [ Fig.…”
Section: Protease Activitymentioning
confidence: 99%
See 1 more Smart Citation